2009
DOI: 10.1094/pdis-93-12-1259
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Soybean withSoybean mosaic virusandAlfalfa mosaic virusResults in Disease Synergism and Alteration in Accumulation Level of Both Viruses

Abstract: Co-infection of potyviruses with taxonomically diverse plant viruses results in disease synergism and elevation in the level of accumulation of non-potyviruses involved. In the majority of cases, however, the accumulation level of potyviruses remains essentially unaltered. A few potyviruses, such as Soybean mosaic virus (SMV), naturally infect soybean (Glycine max). Soybean is also a natural host to a number of non-potyviruses including Alfalfa mosaic virus (AMV), which causes mild symptoms often associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 28 publications
0
27
1
Order By: Relevance
“…The anfibody titers in the sera and their sensitivifies and specificities were evaluated in antigen-coated indirect ELISA (AC-IELISA) (26). SDS-PAGE combined with western immunoblotting (34) were utilized for characterization of the expressed proteins from bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The anfibody titers in the sera and their sensitivifies and specificities were evaluated in antigen-coated indirect ELISA (AC-IELISA) (26). SDS-PAGE combined with western immunoblotting (34) were utilized for characterization of the expressed proteins from bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, two booster injections with a total of 625 渭g of SVNaV-NP were given each with a rest period of 1 month in between. Blood samples were taken at various intervals and the antisera were evaluated by antigen coated indirect-ELISA (AC-IELISA) (Malapi-Nelson et al 2009) using bacterially expressed purified SVNaV-NP (0.1 渭g/well) or sap from naturally infected soybean leaf tissues (1:10 w/v in carbonate buffer, pH 9.6) as antigens. For antiserum titration, serial dilutions were prepared in phosphate buffer saline (PBS; 3.2 mM Na 2 HPO 4 , 0.5 mM KH 2 PO 4 , 1.3 mM KCl, 135 mM NaCl, pH 7.4) containing 0.05% (v/v) Tween 20 and 5% (w/v) non-fat dry milk.…”
mentioning
confidence: 99%
“…Furthermore, while it is beyond the scope of this report, the microring resonator analysis platform is intrinsically multiplexable on account of its origins in semiconductor fabrication, and we have previously shown that multiple biomolecular signatures can be simultaneously quantified from a single sample with no loss in device performance (Qavi and Bailey, 2010; Qavi et al, 2011; Washburn et al, 2010). The prospects of detecting multiple viruses from within a single leaf sample is very attractive for crop diagnostics as co-infection with multiple viruses is known to dramatically increase losses in crop yields (Anjos et al, 1992; Calvert and Ghabrial, 1983; Hobbs et al, 2003; Malapi-Nelson et al, 2009; Ross, 1968; Vance, 1991). Therefore, we feel that the silicon photonic microring resonator platform has the potential to be a powerful analytical tool for agricultural detection applications…”
Section: Resultsmentioning
confidence: 99%